KOMUNIKASI KELOMPOK DI DALAM RUMAH REHABILITASI KELUARGA KEMBANG CAHAYA - Kuswidianti Dharma Prewitasari (Commed : Jurnal Komunikasi dan Media, 2019)
The increasingly modern like-day era, or commonly called the millennial era, is increasingly worrying about the rise of drug abuse. Many users or addicts come from children who are still underage. This is a serious problem for the Indonesian people, because generations are very easily involved in drug abuse cases and other legal actions. Related to drug problems, one step that needs to be done in handling this case by providing rehabilitation to users or addictions through drug use. The most important drug addicts in the rehabilitation center for the former drug addicts. One of the rehabilitation places in the city of Purwokerto under the name Kembang Cahaya Family Community. The Kembang Cahaya Family Community (Kekaca) is a group of organizations that want to use drug addicts in the healing process. Memory is a rehabilitation house for drug addicts who really want to recover on their own volition and not from solicitation. The pattern of family communication in the Messages is very pronounced. Communication that is like a relationship between a father and his children. In addition, activities in rehabilitation are also filled with a variety of positive activities, both spiritual and non-spiritual in order to be converted into the busyness and emptiness of the junkies in a more positive direction. Keywords: Communication, Community, Drugs, Rehabilitation, Kekaca.